2015
DOI: 10.5551/jat.26385
|View full text |Cite
|
Sign up to set email alerts
|

The Serum YKL-40 Level is Associated with Vascular Injury and Predicts Proteinuria in Nephrotic Syndrome Patients

Abstract: Aim: Nephrotic syndrome (NS) is associated with an increased rate of cardiovascular events. The YKL-40 level is associated with atherosclerosis, endothelial dysfunction and proteinuria in renal and non-renal populations. The aim of this study was to investigate the relationships between the YKL-40 level and both vascular injury and proteinuria in NS patients. Methods: Sixty-nine NS patients and 20 healthy subjects were enrolled in the present study. The endothelial function was assessed according to the flow m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The relationship between nephrotic syndrome itself and YKL-40 protein is also very close. YKL-40 can be used as a predictor of urinary protein levels in patients with nephrotic syndrome [25]. In our results, we had found significant correlation between max-CIMT and YKL-40 ( P <0.05).…”
Section: Discussionsupporting
confidence: 55%
“…The relationship between nephrotic syndrome itself and YKL-40 protein is also very close. YKL-40 can be used as a predictor of urinary protein levels in patients with nephrotic syndrome [25]. In our results, we had found significant correlation between max-CIMT and YKL-40 ( P <0.05).…”
Section: Discussionsupporting
confidence: 55%
“… 234 In nephrotic syndrome patients the serum CHI3L1 level is associated with endothelial dysfunction and increased arterial stiffness and may be an indicator of the level of proteinuria in this patient population. 235 …”
Section: Chi3l1 In Urinary Diseasesmentioning
confidence: 99%
“…Furthermore, it has been shown that NS is associated with endothelial dysfunction [4], and as the disease enters remission, endothelial injury improves [5]. Additionally, increased oxidative stress is associated with glomerular injury, resulting in chronic renal injury [6,7]. Researchers all over the world have focused on discovering reproducible, simple, fast, and low-cost biomarkers to evaluate endothelial dysfunction and to determine inflammatory status and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%